CO34 | Evaluation of emicizumab concentration and thrombin generation in a cohort of severe hemophilia A patients with and without inhibitor (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Emicizumab has changed the prophylaxis paradigm of hemophilia A (HA). Despite its fixed-dose, measuring emicizumab plasma concentration ([E]p) may be occasionally useful and the global hemostatic response could be monitored through Thrombin Generation Assay (TGA). Our aim is determining [E]p and TGA parameters and evaluating them across our patient (pt) cohort.